Influence of finishing diet on fatty acid profile in Psoas major muscle of Nero Siciliano pig - Di Rosa A.; Chiofalo V.; Lo Presti V.; Scianò S.; Zumbo A. (7th International Symposium on the Mediterranean Pig, 2012)
Skeletal muscle is a heterogeneous tissue composed of different fibre types, and differences in meat quality traits between "white" and "red" muscles and between certain breeds are well established. Therefore, the study examined the fatty acid composition of the red (Psoas major - PM) muscle in twenty-four Nero Siciliano pigs fed with two different diets. The trial was carried out in the Nebrodi mountain area of Sicily (Italy). During the fattening period, the animals were divided into two groups, kept in two distinct wooded areas of 6 hectares each, and fed exclusively on acorn (A) and germinated barley (B). Results showed that the concentrations of the long chain n-6 and n-3 fatty acids (which were recently found to play an important role in human nutrition) differed significantly between the two groups (P=0.015 for long chain n-6 and P=0.048 for long chain n-3). The linoleic acid (A 5.96 vs B 5.10; P=0.006) and α-linolenic acid (A 0.30 vs B 0.25; P=0.028) were higher in group A. Both group had high concentrations of C18:1 n–9, but in group A (43.27) concentrations were significantly (P=0.006) higher than in group B (40.10).
7. International Symposium on the Mediterranean Pig, 2010/10/14-16, Córdoba (Spain)